Single-Photon Emission Computed Tomography Is an Ambiguous Imaging Method on Initial Diagnosis for Acute Encephalopathy - Yamanaka, Gaku; Morishita, Nastumi; Oana, Shingo; Takeshita, Mika; Morichi, Shinichiro; Ishida, Yu; Kashiwagi, Yasuyo; Kawashima, Hisashi (Neuropediatrics, 2016)
The distinction between acute encephalopathy (AE) and convulsive disorders with pyrexia may be problematic. We analyzed the clinical and laboratory features in 127 children who were admitted for suspected AE. They were categorized into (1) definite acute encephalopathy group (DAEG; n = 17, abnormal findings on electroencephalography [EEG], magnetic resonance imaging, or single-photon emission computed tomography [SPECT] with prolonged impaired consciousness), (2) probable acute encephalopathy group (PAEG; n = 21, abnormal findings without prolonged impaired consciousness), and (3) nonacute encephalopathy group (NAEG; n = 89). Cerebrospinal fluid interleukin-6 (CSF IL-6), and serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), and creatine phosphokinase levels were significantly higher in DAEG compared with NAEG but not PAEG. No significant differences were observed between DAEG and PAEG except for serum creatinine levels. In PAEG, an area of hypoperfusion was observed on SPECT images of nine patients with normal CSF IL-6 levels. AE was suspected in two PAEG patients who exhibited high CSF IL-6 levels and abnormal EEG findings without abnormal SPECT findings. All seven patients with severe neurological sequelae were categorized to DAEG. CSF IL-6 and serum AST, ALT, and creatine kinase levels may be valid predictors of typical AE; prolonged impaired consciousness is an important sign of AE. However, SPECT may not be suitable for initial diagnosis of AE.
Keywords: acute encephalopathy; cytokine; single-photon emission computed tomography; febrile seizures; interleukin-6